Air pollution, genetic factors and the risk of osteoporosis: A prospective study in the UK biobank - Yu, Xing-Hao; Cao, Han-Wen; Bo, Lin; Lei, Shu-Feng; Deng, Fei-Yan (Frontiers in Public Health, 2023)
Purpose To reveal relationship between air pollution exposure and osteoporosis (OP) risk. Methods Based on large-scale data from the UK Biobank, we evaluated the relationship between OP risk and several air pollutants. Then air pollution scores (APS) were constructed to assess the combined effects of multiple air pollutants on OP risk. Finally, we constructed a genetic risk score (GRS) based on a large genome-wide association study of femoral neck bone mineral density and assessed whether single or combined exposure to air pollutants modifies the effect of genetic risk on OP and fracture risk. Results PM2.5, NO2, NOx, and APS were significantly associated with an increased risk of OP/fracture. OP and fracture risk raised with increasing concentrations of air pollutants: compared to the lowest APS quintile group, subjects in the highest quintile group had a hazard ratio (HR) (95% CI) estimated at 1.140 (1.072-1.213) for OP and 1.080 (1.026-1.136) for fracture. Moreover, participants with low GRS and the highest air pollutant concentration had the highest risk of OP, the HRs (95% CI) of OP were 1.706 (1.483-1.964), 1.658 (1.434-1.916), 1.696 (1.478-1.947), 1.740 (1.506-2.001) and 1.659 (1.442-1.908), respectively, for PM2.5, PM10, PM2.5-10, NO2, and NOx. Similar results were also observed for fractures. Finally, we assessed the joint effect of APS and GRS on the risk of OP. Participants with higher APS and lower GRS had higher risk of developing OP. Similar results were observed in the joint effect of GRS and APS on fracture. Conclusions We found that exposure to air pollution, individually or jointly, could improve the risk of developing OP and fractures, and increased the risk by interacting with genetic factors.